Adult intestinal transplantation in the United States. Issue 2 (April 2020) - Iyer, Kishore; Moon, Jang
Abstract : Purpose of review: There has been a striking decline in the annual volumes of adult intestinal transplants performed in the United States from a peak in 2008, reaching its lowest volume in 2019. The current review examines the pattern and potential reasons for the decline. Recent findings: We observe that while improvements in intestinal rehabilitation may be contributing to some of the decline, movements of key personnel and the paucity of experts in a rarefied field may also be contributing to declining volumes. Summary: We suggest that the decline in volumes of adult intestinal transplants are likely to be multifactorial. At a time of improving transplant outcomes, the indications for intestinal transplant suggested by the Centers for Medicare and Medicaid Services, may be outdated and worthy of revision.